Effect of processing conditions in the preparation of PP-Ternary Nanocomposite using MWCNT as secondary filler - Olalekan, Salawudeen Taofeeq; Al-Khatib, Ma'an Fahmi Rashid; Yusof, Faridah; Shah, Qasim Hussain; Muyibi, Suleyman Aremu (David Publishing, 2011)
The present paper investigates the behavior of experimental polypropylene ternary nanocomposites produced in the laboratory under different process conditions using multiwall carbon nanotube as secondary filler. Full factorial experimental design was explored to study the effect of temperature, mixing speed and carbon nanotube (CNT) loading on the morphological and mechanical features of the ternary nanocomposites following the determination of maleic anhydride grafted polypropylene (MAgPP) percentage required for the intermediate composite. Tensile properties and morphological characterization were studied using universal tensile machine (UTM) and scanning electron microscope (SEM) machines respectively. The results revealed that process temperature and CNT loading influences both the morphological and mechanical properties of polypropylene ternary nanocomposites, whereas, the mixing speed has little effect on these properties. Specifically, CNT loading in amount less than 1% showed better tensile strength and stiffness while the strength falls off at 1% CNT loading. Morphological studies indicate better dispersion of CNT in the binary composite system at process temperature of 170 °C and formation of agglomerates at 250 °C. The present study suggests that CNT loading and process temperature lower than 1% and 200 °C respectively produces polypropylene ternary nanocomposites with better mechanical properties and enhanced dispersion of the CNT in the composite system at a moderate mixing speed slightly above 100 rpm.